2013
DOI: 10.1111/tri.12115
|View full text |Cite
|
Sign up to set email alerts
|

Induction therapy in lung transplantation

Abstract: Strategies for induction in lung transplant recipients typically mirror those used in other solid organ transplant recipients. Polyclonal (Atgam, RATG) and monoclonal (OKT3) T-cell depleting agents, IL-2 Receptor antagonists (basiliximab and daclizumab) have been used most commonly. In spite of evidence from ISHLT registry reports that induction reduces acute rejection and has a small benefit in freedom from bronchiolitis obliterans and long-term survival, other studies have been less convincing in terms of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Immunosuppressive protocols following lung transplantation must be modified to take into account certain organ-specific features. Maintaining adequate immunosuppression appears to be particularly important, especially during the immediate post-transplant period, due to various factors such as T-cell activation caused by donor dendritic cell activity and ongoing exposure of the lungs to endogenous antigens [ 162 ]. Acute rejection contributes to the risk of bronchiolitis obliterans syndrome (BOS) [ 163 ], the principal factor limiting long-term graft survival after lung transplantation [ 164 ].…”
Section: Ratg In Lung Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosuppressive protocols following lung transplantation must be modified to take into account certain organ-specific features. Maintaining adequate immunosuppression appears to be particularly important, especially during the immediate post-transplant period, due to various factors such as T-cell activation caused by donor dendritic cell activity and ongoing exposure of the lungs to endogenous antigens [ 162 ]. Acute rejection contributes to the risk of bronchiolitis obliterans syndrome (BOS) [ 163 ], the principal factor limiting long-term graft survival after lung transplantation [ 164 ].…”
Section: Ratg In Lung Transplantationmentioning
confidence: 99%
“…Retrospective analyses of data from the ISHLT registry have shown that induction therapy generally is associated with a reduced risk of BOS, presumably due to reduced rejection [ 162 , 166 , 167 ]. One analysis of ISHLT data [ 158 ] and one based on OPTN data [ 124 ] have indicated higher lung allograft and patient survival with induction versus no induction.…”
Section: Ratg In Lung Transplantationmentioning
confidence: 99%
“…In all three of our subjects, we observed decreases in CD4 levels early after transplantation. In general, IL-2 receptor antagonists, such as basilixumab, do not lead to significant T cell depletion (23). The drop in CD4 1 T cells may be due in part to mycophenolate mofetil (24).…”
Section: Original Researchmentioning
confidence: 99%
“…In fact, clinical immunosuppression protocols depleting T cells indiscriminately in the peri-operative period that have been successful in kidney transplantation have been adapted to lung transplant patients (112). However, we have recently shown that graft infiltration by central memory CD8+ T cells is critical to induce costimulatory blockade-mediated tolerance after lung transplantation in the mouse (113).…”
Section: Introductionmentioning
confidence: 99%